INOCA affects more than the coronaries. (3rd October 2022) - Mailey, J; Moore, J S; Brennan, P F; Jing, M; Awuah, A; McLaughlin, J A D; Nesbit, M A; Moore, C B T; Spence, M S
Abstract: Background: Ischaemia with normal coronary arteries (INOCA) may result in disabling symptoms and has an association with adverse long-term prognosis. The diagnosis of INOCA necessitates invasive coronary angiography to perform a physiological evaluation of microvascular function. The conjunctiva has a readily assessable microvascular network in which physiological parameters can be evaluated. We compared conjunctival haemodynamics in patients with and without coronary microvascular disease (MVD) to assess if systemic microvascular dysfunction was present in this coronary artery disease sub-group. Methods: In this study, we recruited patients undergoing invasive coronary angiography for the investigation of angina or angina equivalent symptoms. All patients had physiologically insignificant epicardial disease (FFR≥0.80) and underwent a physiological evaluation of coronary microvascular function. We compared a group with evidence of coronary MVD (IMR≥25 or CFR<2.0); to a group of controls without MVD (IMR<25 and CFR≥2.0). The conjunctival microvasculature was imaged using a previously validated combination of a smartphone and slit-lamp biomicroscope. The conjunctival vasculature was assessed using a semi-automated process of vessel diameter measurement and erythrocyte tracking to obtain haemodynamic parameters of microvascular function. Results: A total of 111 patients were included (43 MVD and 68 controls). There were no differences in baseline demographics, co-morbidities, epicardial coronary disease severity or regular pharmacological therapies between the groups. Mean coronary flow reserve (CFR) was lower and mean index of microcirculatory resistance (IMR) higher in the MVD cohort (CFR 2.5±1.3 vs 5.2±2.5, p<0.001 and IMR 28.4±11.8 vs 13.7±5.0, p<0.001). A total of 2295 conjunctival vessels were analysed. The mean number of vessels per patient was 21.0±12.8 (3.2±3.5 arterioles and 14.8±10.8 venules). Significant reductions in axial/cross-sectional velocity, wall shear rate and wall shear stress were observed in the MVD cohort. Table 1 demonstrates a comparison of conjunctival physiological parameters between the groups. The most marked differences were observed in conjunctival arterioles. Due to the heterogenous size distribution of microvessels, arterioles were categorised into 2 diameter sub-groups (10–25 μm and 25–40 μm) for analysis (Table 2). Conclusion: The reductions in microvascular blood flow velocity and rate that form the basis for the diagnosis of coronary microvascular dysfunction can be observed non-invasively in the bulbar conjunctiva microcirculation. Conjunctival vascular imaging may have utility as a non-invasive imaging modality to both diagnose microvascular dysfunction and augment conventional cardiovascular risk stratification. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Belfast Trust Heart Trust Fund and Northern Ireland Chest Heart and Stroke